Chest physiotherapy in paediatric patients hospitalised with community-acquired pneumonia: a randomised clinical trial. Issue 11 (21st September 2012) - Lukrafka, Janice Luisa; Fuchs, Sandra C; Fischer, Gilberto Bueno; Flores, José A; Fachel, Jandira M; Castro-Rodriguez, Jose A
Abstract : Background: Chest physiotherapy has been used to treat children hospitalised with pneumonia with no clear scientific evidence to support a beneficial effect. The objective of the current study was to evaluate the efficacy of chest physiotherapy as an adjuvant treatment in children hospitalised with acute community-acquired pneumonia. Methods: Children (aged 1–12 years) with a clinical and confirmed radiological diagnosis of pneumonia sequentially admitted to a tertiary children hospital were eligible for this study. Participants were randomly selected to receive a standardised respiratory physiotherapy (positioning, thoracic vibration, thoracic compression, positive expiratory pressure, breathing exercises and forced exhalation with the glottis open or 'huffing') three times daily in the 'intervention group' or a non-mandatory request to breathe deeply, expectorate the sputum and maintain a lateral body position once a day in the 'control group'. The primary outcomes were reduction in respiratory rate and severity score (respiratory rate, recession, fever, oxygen saturation and chest x-ray) from baseline to discharge. Secondary outcome was duration of hospitalisation. Results: In all, 72 patients were randomly allocated to the intervention (n=35) or control (n=37) groups. There were no differences at admission on severity of pneumonia between groups. Respiratory rate and severity score significant decreased between admission to discharge within each group; however, there were no differences when comparing groups. Also, there was no significant difference in duration of hospitalisation between the control and intervention groups (6 vs 8 days, p=0.11, respectively). Conclusions: This clinical trial suggests that, in children hospitalised with moderate community-acquired pneumonia, chest physiotherapy did not have clinical benefits in comparison to control group.